Root development of pineapple seedlings cultivars inoculated with Fusarium guttiforme isolates - Nunes de Almeida, Rafael; Francelino, Helenilson de Oliveira; Pinto, Luciana Pereira; Gomes, Lavínia Santana Ladeira; Freitas, Marta Simone Mendonça; Vivas, Marcelo (Comunicata Scientiae, 2025)
Fusariosis caused by Fusarium guttiforme is responsible for losses in pineapple production in tropical regions. Information on potential damage to the root system at the early stages of plant development and the magnitude of damage caused by different F. guttiforme isolates is scarce. This study aimed to evaluate the genotype x isolate interaction in pineapple root development. The experimental trial was set up in a randomized block design with four replications in a 4 x 5 factorial arrangement (pineapple cultivars x F. guttiforme isolates + control). The following variables were evaluated at 90 days after inoculation: number of branches, root length, mean root diameter, total root perimeter, root surface area, shoot fresh mass, root fresh mass, shoot dry mass, and root dry mass. The data were subjected to analysis of variance and the means compared by Tukey’s test (p > 0.05). The cultivar Pérola showed a higher reduction in root development when inoculated with F. guttiforme. The cultivars Smooth Cayenne and BRS Vitória showed no changes in root development when inoculated, while ‘IAC Fantástico’ presented damage in the root system when inoculated with the isolates CF/UENF 512, CF/UENF 516, and CF/UENF 528. Pineapple plants may experience reductions in root length, number of branches, and, consequently, root volume when infected by F. guttiforme at the initial stage of development.